Case Report: A Case Report of Stereotactic Ventricular Arrhythmia Radioablation (STAR) on Large Cardiac Target Volume by Highly Personalized Inter- and Intra-fractional Image Guidance - Narducci, Maria Lucia; Cellini, Francesco; Placidi, Lorenzo; Boldrini, Luca; Perna, Francesco; Bencardino, Gianluigi; Pinnacchio, Gaetano; Bertolini, Roberta; Cannelli, Giorgio; Frascino, Vincenzo; Tagliaferri, Luca; Chiesa, Silvia; et al. (Frontiers in Cardiovascular Medicine, 2020)
Introduction Although catheter ablation is the current gold standard treatment for refractory ventricular arrhythmias, sometimes its efficacy is not optimal and it’s associated with high risks of procedural complication and death. Stereotactic arrhythmia radioablation (STAR) is increasingly being adopted for such clinical presentation, considering its efficacy and safety. Case presentation We do report our experience managing a case of high volume of left ventricle for refractory ventricular tachycardia in advanced heart failure patient, by delivering a single fraction of STAR through an highly personalization of dose delivery applying repeated inter- and continuous intra-fraction image guidance. Conclusion According to the literature reports, we recommend considering increasing as much as possible the personalization features and safety technical procedure as long as that is not significantly affecting the STAR duration. Moreover, the duration in itself shouldn’t be the main parameter, but balanced into the frame of possibly obtainable outcome improvement. At best of our knowledge, this is the first report applying such specific technology onto this clinical setting. Future studies will clarify these issues.